INTERNATIONAL EXPERIENCE IN MEASURING THE DIGITAL ECONOMY - A. Abroskin (Вестник университета)
The article considers topical issues of digital economy scales estimates. The results of analysis of the concepts used in international statistics in determining the digital economy as an object of measurement have been presented. Approaches used in international practice to the structuring of the digital segment of the national economy have been adduced. The recommendations of international organizations in the field of methodology for constructing estimates of the scales of digital economy in the system of national accounts have been systematized. Basic methodological approaches to the construction of relevant indicators have been designated. The prospects for improving the methodological and information base for measuring the digital economy have been identified.